Mechanism of Anti-Inflammatory and Antibacterial Effects of QingXiaoWuWei Decoction Based on Network Pharmacology, Molecular Docking and In Vitro Experiments - Zhang, Qian; Li, Xue; Li, Jun; Hu, Yuxia; Liu, Jing; Wang, Fang; Zhang, Wei; Chang, Fuhou (Frontiers in Pharmacology, 2021)
Background and Aim: QingXiaoWuWei Decoction (QXWWD) is a traditional Chinese medicine that is commonly used in clinical settings to treat inflammatory and bacterial diseases. However, there is still a lot to learn about its molecular mechanism. A network pharmacology approach was applied to investigate the pharmacological mechanisms of QXWWD in inflammation treatment. Methods: The basic mechanisms involved in the anti-inflammatory and antibacterial potentials of QXWWD were identified using network pharmacology and molecular docking. The principal components of QXWWD were identified by the HPLC-Q-Exactive-MS method. The antibacterial bioactivity of QXWWD was further investigated using the Kirby-Bauer disc diffusion method and the determination of the minimum inhibitory concentration. The anti-inflammatory activity of QXWWD was evaluated using mice ear swelling test, RAW264.7 cell culture, and pro-inflammatory cytokines measurement. Skin irritation and HE staining were employed to evaluate the safety of QXWWD topical use and to depict the drug's potential therapeutic function. The hub genes and signaling pathways associated with inflammatory and bacterial diseases were validated by western blot in addition to biochemical and pathological markers. Results: Our findings revealed that the ethanolic extract of QXWWD had a strong inhibitory effect against Staphylococcus aureus, Enterococcus faecalis, and Streptococcus pneumoniae. Meanwhile, QXWWD was potentially effective in suppressing ear swelling, elevated white blood cell counts, and the TNF-α, IL-1, and IL-6 levels. According to skin irritation, QXWWD was found to be safe when tested for topical application. The results of HE staining showed that the possible therapeutic role of QXWWD was related to the change in skin microstructure. Also, the network pharmacology, molecular docking as well as Q-Exactive-MS and HPLC analysis suggested that the synergistic effect of quercetin, luteolin and other ingredients could serve as main contributor of QXWWD for its anti-inflammatory and antibacterial activities. Moreover, the JUN, MAPK1, RELA, NFKBIA, MYC, and AKT1 were the potential identified key targets, and MAPK/PI3K/Akt was among the possibly involved signaling pathways in the anti-inflammatory and antibacterial activities of QXWWD. Conclusions: From a therapeutic standpoint, QXWWD may be a promising antibacterial and anti-inflammatory agent for the treatment of bacterial, acute, and chronic dermatitis.